2019
DOI: 10.1145/3312743
|View full text |Cite
|
Sign up to set email alerts
|

Single- and Multi-FPGA Acceleration of Dense Stereo Vision for Planetary Rovers

Abstract: Increased mobile autonomy is a vital requisite for future planetary exploration rovers. Stereo vision is a key enabling technology in this regard, as it can passively reconstruct in three dimensions the surroundings of a rover and facilitate the selection of science targets and the planning of safe routes. Nonetheless, accurate dense stereo algorithms are computationally demanding. When executed on the low-performance, radiation-hardened CPUs typically installed on rovers, slow stereo processing severely limit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…VisLoc (Shaw, Woods, Churchill, & Newman, 2013), developed during the ExoMars mission and based on the Oxford visual odometry (OVO) algorithm (Churchill & Newman, 2012), and SPARTAN (Kostavelis, Boukas, Nalpantidis, Gasteratos, & AvilesRodrigalvarez, 2011, 2014), developed under a series of ESA R&D activities during the last decade. In addition, latest works in SPARTAN made a significant effort toward optimizing and efficiently bringing localization and mapping processes to space representative FPGA hardware implementations (Avilés et al, 2018; Lentaris, Maragos, Soudris, Zabulis, & Lourakis, 2019). ExoMars‐like field test campaigns have been run in the Atacama Desert to increase the technology readiness level (TRL) of these technologies.…”
Section: Introductionmentioning
confidence: 99%
“…VisLoc (Shaw, Woods, Churchill, & Newman, 2013), developed during the ExoMars mission and based on the Oxford visual odometry (OVO) algorithm (Churchill & Newman, 2012), and SPARTAN (Kostavelis, Boukas, Nalpantidis, Gasteratos, & AvilesRodrigalvarez, 2011, 2014), developed under a series of ESA R&D activities during the last decade. In addition, latest works in SPARTAN made a significant effort toward optimizing and efficiently bringing localization and mapping processes to space representative FPGA hardware implementations (Avilés et al, 2018; Lentaris, Maragos, Soudris, Zabulis, & Lourakis, 2019). ExoMars‐like field test campaigns have been run in the Atacama Desert to increase the technology readiness level (TRL) of these technologies.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, we i) develop the first FPGA implementation of the plane sweep stereo vision algorithm in the literature, and ii) we introduce a multi-FPGA partitioning methodology for design mapping onto multiple FPGAs. We clarify that this work [77] is the product of European Space Agency (ESA) funded projects, namely SEXTANT 1 and COMPASS 2 , with the thesis author's contributions being on the HW implementation and HW analysis of specific components of plane sweep algorithm (in Fig. 3.2, MNCC calculator, depth map and temp store), the development of multi-FPGA partitioning methodology and the integration of HW architecture on the multi-FPGA platform.…”
Section: Stereo Vision For Rover Navigationmentioning
confidence: 99%
“…3.2, MNCC calculator, depth map and temp store), the development of multi-FPGA partitioning methodology and the integration of HW architecture on the multi-FPGA platform. The SW development and analysis of the plane sweep algorithm was performed by Foundation for Research and Technology -Hellas (FORTH) and in-depth details can be found in [77].…”
Section: Stereo Vision For Rover Navigationmentioning
confidence: 99%
See 2 more Smart Citations